2015
DOI: 10.1007/s13277-015-3077-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SMYD3 and matrix metalloproteinase-9 are associated with poor prognosis of patients with gastric cancer

Abstract: SET and MYND domain-containing protein 3 (SMYD3) plays a key role in the progression of human cancer. Matrix metalloproteinase (MMP)-9 is being related to tumor progression. It has been reported that SMYD3 and MMP-9 are overexpressed in human cancers. However, the exact roles of SMYD3 and MMP-9 in the metastasis and prognosis of gastric cancer (GC) remain unclear. The expressions of SMYD3 and MMP-9 were detected by semiquantitative reverse transcription polymerase chain reaction and Western blotting in gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…MMPs are critical players in tumor migration and invasion through degradation of ECM components. Other studies have shown that MMP-2 expression is significantly relevant for the tumor metastasis (35) and expression of MMP-9 is closely related to poor prognosis and metastasis of CRC (36). MMP-2 and MMP-9 are frequently upregulated in cancer cells (37,38).…”
Section: Discussionmentioning
confidence: 96%
“…MMPs are critical players in tumor migration and invasion through degradation of ECM components. Other studies have shown that MMP-2 expression is significantly relevant for the tumor metastasis (35) and expression of MMP-9 is closely related to poor prognosis and metastasis of CRC (36). MMP-2 and MMP-9 are frequently upregulated in cancer cells (37,38).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, the liver and breast human cancer sample dataset from the "The Cancer Genome Atlas" (TCGA) revealed that SMYD3 transcript levels correlate with expression of key proliferation [18] and EMT genes [18,35]. In addition, SMYD3 expression was positively associated, respectively, with the metalloproteinases MMP-2 and MMP-9 expression in pancreatic and gastric cancer tissues [92,93].…”
Section: Mouse Experimental Model Pancreatic Ductal and Lung Adenocarmentioning
confidence: 99%
“…Previous results have shown that SMYD3 is expressed differentially in normal and cancer tissues (21)(22)(23)(24). SMYD3 overexpression has been associated with progression in gastric and breast cancer (23,25). However, the effect of altered SMYD3 expression on the progression of glioma cells remains elusive.…”
Section: Discussionmentioning
confidence: 99%